A comparative analysis of the impacts of digital lifestyles on the physical, mental, and social health among older internet users - Bin Wang (Humanities & Social Sciences Communications)
Abstract The Internet has become integral to contemporary lifestyles. Drawing definitive conclusions about the impact of digital lifestyles on the health of older Internet users is challenging because of conflicting research findings. This study proposes the prismatic effects framework that demonstrates superior applicability to older Internet users in China. A nationally representative sample of Internet users aged 60 years or older (N = 2085) from the 2018 China Longitudinal Ageing Social Survey was used in the analyses. Latent class analysis was employed to identify digital lifestyles through ten activities, and the augmented inverse probability weighted model was adopted to explore the association of digital lifestyles with physical, mental, and social health among older Internet users. Meaningful digital lifestyles were identified as follows: low-activity (12.71%), high-activity (5.95%), leisure activity (33.67%), and social activity groups (47.67%). The low-activity group indicated better physical health than the social activity group (Average Treatment Effect (ATE) = −0.12, 95% Confidence Interval (CI) = −0.23, −0.01). The high-activity group had lower depressive symptoms (ATE = −1.51, 95% CI = −2.23, −0.80) than did the low-activity group. Moreover, the high-activity (ATE = −0.58, 95% CI = −0.95, −0.22) and leisure activity (ATE = −0.34, 95% CI = −0.62, −0.05) groups demonstrated lower loneliness than did the low-activity group. The low-activity group had a higher risk of friend isolation than did the social activity group (ATE = −0.17, 95% CI = −0.30, −0.05) but more community involvement than the high-activity group (ATE = −0.23, 95% CI = −0.38, −0.08). These findings support the prismatic effects framework and reveal that the health effects of digital lifestyles are multidimensional with different potential benefits and harms across health dimensions. The nature of digital lifestyles may be more critical than digital access from a health outcome perspective.